1999
DOI: 10.1038/sj.bmt.1701957
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow transplantation for high risk acute lymphoblastic leukemia: clinical relevance of ex vivo bone marrow purging with monoclonal antibodies and complement

Abstract: Summary:Herein we describe our experience with 75 consecutive autologous BM transplants for patients with high-risk ALL, with special attention to the clinical impact of BM purging. Fifty-two patients received purged BM using monoclonal antibody (MoAb) cocktails and complement, and 23 patients received untreated BM. The distribution of prognostic factors was similar in both groups. Hemopoietic reconstitution was adequate and did not differ in the two groups. Transplant-related mortality was 9.6% and 13% in 'pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…[43][44][45][46] This study compares favorably with previous experiences using chemotherapy and historical unmanipulated autografting, reporting EFS ranging from 33 to 56% for CNS relapses, 69% for any extramedullary relapse and from 41 to 61% for late relapses. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] In a previous matched-pair analysis for late medullary relapses, autologous transplantation, reporting an EFS of 41%, was of no benefit, compared with chemotherapy. 20 Patient selection may differ, as T-lineage ALL was excluded from this B-lineage ALL study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[43][44][45][46] This study compares favorably with previous experiences using chemotherapy and historical unmanipulated autografting, reporting EFS ranging from 33 to 56% for CNS relapses, 69% for any extramedullary relapse and from 41 to 61% for late relapses. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] In a previous matched-pair analysis for late medullary relapses, autologous transplantation, reporting an EFS of 41%, was of no benefit, compared with chemotherapy. 20 Patient selection may differ, as T-lineage ALL was excluded from this B-lineage ALL study.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were performed by SAS and S-plus. (24) or 2000 (5) frontline protocols; one patient was treated abroad. [35][36][37][38] Mobilization, collection, purification Thirty-one patients were actually enrolled in the mobilization protocol and underwent autologous transplant.…”
Section: Manipulation Of the Graftmentioning
confidence: 99%
See 1 more Smart Citation
“…Some retrospective reports, mostly performed in patients actually receiving ASCT and not based on the intent-to-treat principle, have suggested that ASCT may be associated with prolonged DFS. [17][18][19][20][21][22][23][24][25] However, reported prospective studies enrolling either standard-risk (Truchan-Graczyk et al Blood 2002; 100: 861a, abstract), high-risk, 26,27 or all-risk ALL patients 1,2,28 (and Rowe et al Blood, 2001; 98, 481a, abstract) failed to demonstrate the superiority of ASCT over chemotherapy, perhaps because of the relatively limited populations of patients randomized.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown 1,2 that results of autologous hematopoietic stem cell transplantation (HSCT) in adult ALL [3][4][5][6][7][8][9][10][11][12][13][14] can be improved by administering post transplant maintenance chemotherapy with 6-mercaptopurine (6-MP), methotrexate and vincristine-prednisone. A recent review of autologous HSCT in ALL 15 suggested that the value of autotransplantation is likely to be underestimated in ALL.…”
Section: Introductionmentioning
confidence: 99%